CVC Nickel Project Corporation a design project - Valin, Virgilio (College of Engineering, 1971)
Initial capital requirement: 63 million -- Operating capital (cash and inventory): 3.4 million -- Expected pay-out time: 4 years -- Capacity: 2,160,000 tons/year -- Sales at capacity: 65,243,520 -- Break-even point: 45% capacity -- Shut-down point: 3.96% capacity